A semi-analytical approach for efficient calculation of drained cross-anisotropic elastic moduli in saturated granular soils from undrained attributes. (August 2022) - Pegah, Ehsan; Liu, Huabei; Gu, Xiaoqiang; Gholami, Ali
Abstract: The anisotropic elastic parameters in granular soil deposits possess a fundamental contribution in the analysis of many geotechnical engineering problems. In this study, the feasibility of estimating the drained elastic moduli in saturated granular soils was examined based on the undrained properties. By assuming cross-anisotropic properties in granular soil, a series of theoretical equations coupled with the experimental correlations in literature were obtained representing the relationships between drained and undrained elastic parameters. A new approach was consequently developed to estimate the anisotropic drained Young's moduli based on two anisotropic components of shear moduli and vertical component of Young's modulus in the undrained conditions. To inspect the validity of proposed approach, the anisotropic elastic properties resulting from 47 conducted laboratory tests on 7 different granular soil specimens relating to 3 various soil types from distinct locations in the world were collected from literature. The anisotropic drained Young's moduli in each test were evaluated by the suggested method and then compared with directly measured values, which revealed a reasonable agreement. The findings of this study can be utilized as a reference for reasonable and inexpensive characterization of in-situ anisotropic elastic stiffness parameters of saturated granular soil deposits through the non-destructive seismic techniques.